Comparison between soccer players in fundamental skill from different position - Campos, P.; Junior, A. F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The athletes` performance and accuracy from the basics movements it may interfere on the match results, using the premises that the team with the best average in the fundamentals has the best probability of a positive result. The purpose of this study was to evaluate and compare four basics soccer fundamentals in a group of soccer players who plays in a different position. Methodology: The experimental group of 20 Brazilian male soccer player (mean age 16,3) were tested throughout a 4 basic soccer fundamental in a field test. The fundamentals tested were accuracy shooting, accuracy pass, conducting the ball and penetration throughout obstacles without the ball and with the ball. Group 1 consisted of four fullbacks, group 2 four halfbacks, group 3 four wings, group 4 four midfield and group 5 four forward. Accuracy shooting: consisted of an unobstructed divided goal in 6 quadrants target with different punctuation. The participants were asked to take four shots from a set distance away in 15 seconds. Accuracy pass over a short distance: This test is handicapped by the amount of time a subject has to complete the course. The test was designed so that each pass should be done with alternative feet, left right, left right or visa versa. A participant must score maximum accuracy points before time. Penetration throughout obstacles without the ball and with the ball: this test was designed to improve close control while at pace without and with the ball. Eight cones are set out in a slalom effect and a single cone is placed a set distance. The idea was for the subject to run the slalom course up and down, with(out) the ball at his feet to the other designated cone. Results: Observed differences occurred during the Penetration throughout obstacles without the ball were: the wings (mean 7,4 ±0,7 m/s); the fullbacks (7,2 ± 0,2 m/s); the halfbacks (7,5 ± 0,9 m/s); midfielders (7,4 ± 0,6 m/s); and (7,1 ± 0,7 m/s) for the forwards. No significant difference were found between the groups p<0,05. Penetration throughout obstacles with the ball the mean were for: the wings (11,4 ± 1,9 m/s) ; fullbacks (10,9 ± 1,4 m/s); halfbacks (10,9 ± 1,3 m/s); midfield ( 9,9 ± 1,6 m/s) and (9,3 ± 2,3 m/s) for the forwards. A significant difference were found t student p<0,05 between the wings players and forwards. Conclusion: the forwards players appear to posses a better speed in the penetration run throughout obstacles with the ball among the others groups. This could be especially important because the speed and the fundamentals skills based on the level of the game and the player can make the difference during the match.